Stimuli-Responsive Gold Nanoparticles for Cancer Diagnosis and Therapy - Tian, Li (J Funct Biomater, 2016)
An emerging concept is that cancers strongly depend on both internal and external signals for growth and invasion. In this review, we will discuss pathological and physical changes in the tumor microenvironment and how these changes can be exploited to design gold nanoparticles for cancer diagnosis and therapy. These intrinsic changes include extracellular and intracellular pH, extracellular matrix enzymes, and glutathione concentration. External stimuli include the application of laser, ultrasound and X-ray. The biology behind these changes and the chemistry behind the responding mechanisms to these changes are reviewed. Examples of recent in vitro and in vivo studies are also presented, and the clinical implications of these findings are discussed.